The Place of Money Capital in the Theory of Production - Gabor, Andre; Pearce, I. F. (Quarterly Journal of Economics, 1958)
I. Outline of the problem of capital and of the need to reconcile its treatment by Austrian and neoclassical theorists, as also to establish a link between economics and accountancy practice, 537. — II. Introduction to the concept of the money capital requirement function and the criteria of profit rate maximization, 540. — III. Synthesis of divergent theories by full development of a new generalized money capital requirement function, 544. — IV. Comparison of the results here obtained with those of neoclassical theory, 555. — V. Summary, 557. <qd> “Capital is not in the technical sense just another factor juxtaposited with the primary factors, but rather a new dimension on each of the primary factors.” (Ragnar Frisch.)1 </qd>